A MEASURING THE FINANCIAL RATIO OF BNI SYARIAH BANK USING CAMEL ANALYSIS - Elfina Damanik; Sartika; Risma Nuraini munthe; Desman Serius Nazara (Jurnal Mantik, 2022)
This study was conducted to determine the soundness of BNI Syariah Bank when reviewed using CAMEL analysis. As stated in Article 3 of Bank Indonesia Regulation Number 9/1/PBI/2007, the financial ratios used to measure the health of a bank are Capital, Asset, Management, Earning, and Liquidity (CAMEL). The research method used is the quantitative method, with data analysis of CAR, KAP, NPM, REO, ROA, CR. With 5 composite ratings, rating 1 reflects the bank is classified as very good, rating 2 is classified as good, rating 3 is quite good, rating 4 is classified as poor, and rating 5 is sensitive. The results of this study in 2017 received a Healthy predicate with a final score of 91.2 from the CAMEL factor, in 2018 it received a final score of 89.8 with a healthy predicate, in 2019 it received a final score of 88.7 with a healthy predicate, and in 2020 it received a healthy predicate. final score of 83.8 with a healthy predicate